THE RELATIONSHIP BETWEEN ECONOMY AND ENVIRONMENT IN THE LEGAL AMAZON: AN ANALYSIS BASED ON THE ENVIRONMENTAL KUZNETS CURVE FOR THE YEARS 2002 TO 2020 (REMUNOM, 2025)
The Amazon remained virtually untouched until the inauguration of the Trans-Amazonian Highway in the 1970s. With incentives from the federal government for the occupation of the territory and subsequently the contribution of the productive sector, deforestation rates increased. Currently, climate change is more prominent in the news, and the debate has gained momentum, especially regarding the damage caused by wildfires. This study conducted a literature review on the applicability of the Environmental Kuznets Curve in the Brazilian Legal Amazon. Subsequently, the impact of economic activities on deforestation in the region was verified from 2002 to 2020, using data on GDP per capita, Gross Value Added by economic sector (Agriculture, Industry, Services, and Public Administration), and proxies for deforestation in the region (annual deforestation rates, annual increase in deforestation, and accumulated deforestation), obtained, respectively, from SIDRA-IBGE and PRODES-INPE. The analysis was performed using multiple regression with panel data, estimating the relationship between economic growth and deforestation. Ordinary least squares (OLS) estimation, using the multiple coefficient of determination R², verified the model that best explains the relationship between environmental damage and economic growth, using the accumulated deforestation index as the dependent variable and GDP per capita – linear, quadratic, and cubic – and the GVA of the agricultural and industrial sectors, on a logarithmic basis, as independent variables. Panel data diagnostic tests indicated the Fixed Effects model as the most suitable. The equation estimated by the model showed an inverted “N” CKA shape, indicating an initial scenario in which increased income causes a decline in deforestation levels up to a certain point, where this increase implies a resumption of deforestation and subsequently a new decline. The possibility of this movement becoming cyclical in the long term cannot be ruled out. The results obtained showed a curve shape different from that proposed in the theory, which may be related to the variables and time period selected in the study.